UMP holds life-saving programme to inculcate culture of empathy - Nauwar, Ali (2019)
Universiti Malaysia Pahang (UMP) recently held a “Let’s be a Hero” programme, coordinated by its student representatives from the Residential College 3 (PEKA 3), in collaboration with the university’s Gambang Campus Health Centre, Tengku Ampuan Afzan Hospital (HTAA) and the Kuantan District Dental Care Centre.